Exploiting the Reactivity of 1,2-Ketoamides: Enantioselective Synthesis of Functionalized Pyrrolidines and Pyrrolo-1,4-benzodiazepine-2,5-diones - Acosta, Paola; Becerra, Diana; Goudedranche, Sébastien; Quiroga, Jairo; Constantieux, Thierry; Bonne, Damien; Rodriguez, Jean (Synlett, 2015)
A new strategy for the synthesis of optically active pyrrolo[1,4]benzodiazepine-2,5-diones has been developed. The approach is based on an initial Michael addition of functionalized 1,2-ketoamides on nitroalkenes, with a reduction–double cyclization sequence leading to the desired substituted benzodiazepine.
Keywords: enantioselective Michael addition; benzodiazepine; 1,2-ketoamides